2016
DOI: 10.18632/oncotarget.8746
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PHLPP2/cyclin D1 protein translation contributes to the tumor suppressive effect of NFκB2 (p100)

Abstract: Although the precursor protein of NFκB2 (p100) is thought to act as a tumor suppressor in mammalian cells, the molecular mechanism of its anti-tumor activity is far from clear. Here, we are, for the first time, to report that p100 protein expression was dramatically decreased in bladder cancers of N-butyl-N-(4-hydroxybutyl)-nitrosamine (BBN)-treated mice and human patients. Knockdown of p100 in cultured human bladder cancer cells promoted anchorage-independent growth accompanied with elevating abundance of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…As an identified tumor suppressive gene, multiple lines of evidence reveal the role of PHLPP2 in tumor progression . PHLPP2 is involved in the inhibition of malignant behaviors of cancer attributed to the suppression of prosurvival signaling such as through the PI3K/Akt signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an identified tumor suppressive gene, multiple lines of evidence reveal the role of PHLPP2 in tumor progression . PHLPP2 is involved in the inhibition of malignant behaviors of cancer attributed to the suppression of prosurvival signaling such as through the PI3K/Akt signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PHLPP2 can dephosphorylate and stabilize the Myc oncogene to suppress the progression of prostate cancer . A recent study reported on a novel molecular cascade of PHLPP2/CREB/miR‐302d that mediates cell cycle progression and anchorage‐independent growth . Therefore, the identification of PHLPP2 as an effective prognostic biomarker is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…4d). As a precursor of p52, p100 could function in p52-independent fashion [37]. Thus, we next evaluated the potential contribution of p100 to EGFR expression by ectopic expressing p100 in T24T cells.…”
Section: Resultsmentioning
confidence: 99%
“…The miR-200a knockdown plasmid was purchased from GeneCopoeia (Rockville, MD, USA). The overexpression of HA-∆RING plasmid, the TAM67 plasmid, a well-characterized dominant-negative c-Jun mutant, and the p100 overexpression plasmid were described in our previously studies [19, 36, 37]. Wild-type EGFR 3′-UTR luciferase reporter is a kind gift from Professor Benjamin Purow (University of Virginia Health System, VA) [38].…”
Section: Methodsmentioning
confidence: 99%
“…14 and tumor suppressor genes. 15 Although our most recently studies demonstrate that p100 but not p52, inhibits BC growth by targeting Cyclin D1 protein translation through PHLPP2/CREB/miR-302d axis, 16 the potential participation and molecular mechanisms underlying p52 regulation of BC cell invasion have not been characterized.…”
mentioning
confidence: 97%